Finite Element Analysis of Reinforced Self Consolidation Concrete Beams Having a Horizontal Construction Joint - Abdulmunaam, Muhaj Mustafa; Farhan, Omar Shamal (Al-Nahrain Journal for Engineering Sciences, 2024)
Construction joints are separations between successive concrete pours. They are critical in the building of large concrete structures, since these structures cannot be cast in a single pour. Self-consolidation concrete is a relatively new kind of concrete that is considered suitable for a wide range of construction applications, especially those needing a high early resistance. Certain findings from earlier experimental tests were adopted and analyzed using finite element analysis. ANSYS program was used to analyze the impact of utilizing high strength concrete (fc’) and the secondary reinforcement ratio (ρv) on the behavior of reinforced self-consolidating concrete beams having a horizontal construction joint. Nine beams analyzed in this study have the same dimensions (150×180×1200) mm (width× height ×length). Between the two supports, the clear span was 1100 mm. Two-point loads were applied to the simply supported beams during testing. One of the beams acts as a control beam (without a construction joint) and the remaining beams were with horizontal construction joint in the tension zone. The ultimate loads obtained analytically vary by between 3.1% and 7.8 % from those found experimentally. The presence of the horizontal construction joints made the beam less stiff. Utilizing a 70 MPa high strength concrete resulted in a 47.4 % in ultimate load over the experimental value for regular strength concrete (28 MPa). Increasing the ratio of secondary reinforcement (0.01229 to 0.049) resulted in a 10.3% increase in ultimate load magnitude, while decreasing the ratio of secondary reinforcement (0.01229 to 0.0025) with spanning the spacing between stirrups led to a reduction in ultimate load magnitude by 55.8%.